Virus západonilské horecky (west Nile virus) - Lásiková, S; Moravcová, L; Pícha, D; Horová, B (Epidemiologie, mikrobiologie, imunologie, 2006)
West Nile virus (WNV) is a member of the Flaviviridae family, genus Flavivirus. Its reservoir hosts are wild birds. Infection is transmitted to humans by infected mosquitoes of the genus Culex. In most cases, it is either asymptomatic or manifests itself as mild fever. Typically, WNV illnesshas a sudden onset with fever above 39 degrees C and accompanying symptoms such as chills, headache, arthralgia, myalgia, back ache, cough and sore throat. Gastrointestinal symptoms are frequently reported. Generalized lymphadenopathy and conjunctivitis may develop. In some patients the infection can progress to meningoencephalitis. Diagnosis is currently based on detection of IgM antibodies in blood and cerebrospinal fluid or direct detection of WNV RNA.
Keywords: západonilská horečka; Humans; virus západního Nilu; West Nile Fever; lidé; West Nile virus